Lumpy skin disease: history, current understanding and research gaps in the context of recent geographic expansion - Mazloum, Ali; Van Schalkwyk, Antoinette; Babiuk, Shawn; Venter, Estelle; Wallace, David B.; Sprygin, Alexander (Frontiers in Microbiology, 2023)
Lumpy skin disease is recognized as a transboundary and emerging disease of cattle, buffaloes and other wildlifewild ruminants. Being initially restricted to Africa, and since 1989 the Middle East, the unprecedented recent spread across Eurasia demonstrates how underestimated and neglected this disease is. The initial identification of the causative agent of LSD as a poxvirus called LSD virus, was well as findings and knowledge gaps on LSDV transmission and epidemiology were pioneered at Onderstepoort, South Africa, from as early as the 1940s by researchers such as Weiss, Haig and Alexander.As more data emerges from an ever-increasing number of epidemiological studies, previously emphasized research gaps are being revisited and discussed.The currently available knowledge is in agreement with the previously described Field Code Changed Field Code Changed 1 South African research experience, that LSDV transmission can occur by multiple routes, including indirect contact, shared water sources and arthropods.The virus population is prone to molecular evolution, generating novel phylogenetically distinct variants resulting from a diverse range of selective pressures, including recombination between field and homologous vaccine strains in cell culture that produce virulent recombinants which pose diagnostic challenges. Host restriction is not limited to livestock, with some wildlife speciescertain wild ruminants being susceptible, with unknown consequences for the epidemiology of the disease.